Intriguing aural foreign body and algorithm of management of foreign body - Ponnuvelu, Komalar; Saniasiaya, Jeyasakthy; Abdul Gani, Norhaslinda (BMJ case reports, 2021)
Foreign body (FB) in the external auditory canal is more common among the paediatric age group compared with adult patients and it may be deposited in various ways. An accidental animate aural FB is reported to be commonly encountered in adults whereas inanimate FBs are likely to be found among adult patients with learning disability. An elderly man presented with accidental penetration of rattan tree stem into his ear while gardening. Removal of a FB from the external auditory canal requires expertise as deep penetration of a FB into the middle and inner ear may lead grave complications, especially when overzealous removal is attempted by nonear, nose and throat (ENT) personnel. This case emphasises on the importance of awareness of meticulous removal of a FB under proper visualisation so as to avoid unnecessary complications. Additionally, we propose an algorithm for proper removal of aural FB in an acute care setting.